PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR TEKNIK LISTRIK DASAR OTOMOTIF SISWA KELAS X TEKNIK KENDARAAN RINGAN DI SMK MUHAMMADIYAH I MOYUDAN SLEMAN TAHUN AJARAN 2015/2016 - Havidan Irza Saputra; Subagyo Subagyo (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study was to improve (1) the learning motivation and (2) the learning achievement of automotive basic electrical technique. This type of research was classroom action research. Data collection techniques in this class action research used questionnaires and tests. Data analysis techiques used descriptive and quantitative analysis to determine the percentage of learning outcomes. The results showed that: (1) the studentsâ€™ learning motivation was increased from the first cycle, second cycle and third cycle. From the results obtained in the first cycle the average score = 49.8 in the interval 49 - 63 with a lower category. The second cycle of research results obtained by the average score = 56.35 in the interval 49 - 63 with a lower category. From the results obtained in the third cycle the average score Â (Means) = 69 in the interval 91 - 112 with category; (2) Results of studying electrical engineering automotive base increased after learning methods Problem Based Learning. The test results on the first cycle there were 18 (45%) of students in the first cycle with an average score 65.5. Based on the test results of the second cycle, the score of the average of 74.4 by the number of students who completed was 24 students with a percentage of 60%. Based on the test results of the third cycle, the score of the average of 91.9 by the number of students who completed was 35 students with a percentage of 87.5%. Based on the above, it can be concluded that the PBL method can improve learning outcomes basic automotive electrical technique.